The immunomodulatory role of syncytiotrophoblast microvesicles. - Southcombe, J; Tannetta, D; Redman, C; Sargent, I (2011)
Immune adaptation is a critical component of successful pregnancy. Of primary importance is the modification of cytokine production upon immune activation. With the discovery that normal pregnancy itself is a pro-inflammatory state, it was recognised that the classical Th1/Th2 cytokine paradigm, with a shift towards 'type 2' cytokine production (important for antibody production), and away from 'type 1' immunity (associated with cell mediated immunity and graft rejection), is too simplistic. It is now generally agreed that both arms of cytokine immunity are activated, but with a bias towards 'type 2' immunity. Many factors are released from the placenta that can influence the maternal cytokine balance. Here we focus on syncytiotrophoblast microvesicles (STBM) which are shed from the placenta into the maternal circulation. We show that STBM can bind to monocytes and B cells and induce cytokine release (TNFα, MIP-1α, IL-1α, IL-1β, IL-6, IL-8). Other cytokines are down-modulated, such as IP-10 which is associated with 'type 1' immunity. Therefore STBM may aid the 'type 2' skewed nature of normal pregnancy. We also observed that PBMC from third trimester normal pregnant women produce more TNFα and IL-6 in response to STBM than PBMC from non-pregnant women, confirming that maternal immune cells are primed by pregnancy, possibly through their interaction with STBM.